2012
DOI: 10.1177/0018726712453471
|View full text |Cite
|
Sign up to set email alerts
|

Proactive personality and job performance: The role of job crafting and work engagement

Abstract: The article examines the role of proactive personality in predicting work engagement and job performance. On the basis of the literature on proactive personality and the job demands-resources model, we hypothesized that employees with a proactive personality would be most likely to craft their own jobs, in order to stay engaged and perform well. Data were collected among 95 dyads of employees (N = 190), who were working in various organizations. The results of structural equation modeling analyses offered stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
874
3
44

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 911 publications
(986 citation statements)
references
References 59 publications
(82 reference statements)
65
874
3
44
Order By: Relevance
“…Previous studies have found a relationship between job crafting and well-being and performance (e.g. Bakker et al, 2012;Leana et al, 2009;Petrou et al, 2012;. In the present study, we aim to confirm some patterns previously tested using the JCRQ as we explore the relationship between job crafting and job satisfaction using survey data from China, Spain, Taiwan and the UK.…”
Section: Study 4: Job Crafting and Its Relationship With Well-being Asupporting
confidence: 54%
“…Previous studies have found a relationship between job crafting and well-being and performance (e.g. Bakker et al, 2012;Leana et al, 2009;Petrou et al, 2012;. In the present study, we aim to confirm some patterns previously tested using the JCRQ as we explore the relationship between job crafting and job satisfaction using survey data from China, Spain, Taiwan and the UK.…”
Section: Study 4: Job Crafting and Its Relationship With Well-being Asupporting
confidence: 54%
“…To simplify our model and consistent with our hypotheses, we followed the approaches of Bakker et al (2012) and Tims et al (2015) and we modelled job crafting using two latent factors. The first factor contained the residual mean scores of increasing structural job resources, increasing social job resources, and increasing challenging job demands ("crafting more job resources and challenging job demands").…”
Section: Analysis Strategymentioning
confidence: 99%
“…Therefore, on the basis of person-environment fit theory (Edwards, 2008), this congruence between needs and environment achieved through job crafting is expected to promote employees' engagement at work. In addition, a number of authors have established a positive relationship between proactive behaviours such as job crafting, personal initiative, feedback-seeking and self-development, and positive outcomes such as work engagement and positive emotion (Anseel, Beathy, Shen, Lievens & Sackett, 2013;Bakker et al, 2012;Hyvonen, Feldt, Salmela-Aro, Kinnunen & Makikangas, 2009;Ko, 2012;Tims et al, 2013).…”
Section: Question 4: How Does the Interplay Of Job Resources And Jobmentioning
confidence: 99%
“…Therefore, on the basis of person-environment fit theory (Edwards, 2008), this congruence between needs and environment achieved through crafting is expected to promote employees' engagement at work. Bakker et al (2012) for example, found job crafting (as indicated by increasing structural and social resources and challenge demands) to predict both work engagement and in-role performance. Further analysis demonstrated that increasing structural resources was the strongest of the crafting dimensions in predicting these positive outcomes.…”
Section: Job Crafting and Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation